Combustion process in a biomass grate fired industry furnace: a CFD study. (4th August 2006) - Klason, T.; Bai, X.S.
This paper presents a CFD investigation of the combustion process in a 50 MW grate fired furnace. The CFD results were compared with available experimental data at the furnace outlet to validate the models for the volatile oxidation and NOx formation. The models were then used to predict the effect of an 'ECO' tube system on NOx emissions. It was shown that with an improved flow structure and air distribution, 30%; NOx reduction can be obtained. CFD results revealed the impact of load and fuel moisture on the flow structure, the temperature distribution and the flow residence time.